THE EFFECT OF PEER ASSESSMENT TOWARDS STUDENTS’ SPEAKING SKILL AT SEMESTER II OF STIE MUHAMMADIYAH JAMBI 2018-2019 - Syilvia Wenny J; Rahmat Fajar (Celtic : A Journal of Culture, English Language Teaching, Literature and Linguistics, 2019)
Speaking subject performed at colleges, especially English language courses, is provided to students to actively develop English speaking skills. However, in fact there are still many students who are less taking advantage of the opportunities given. This has an impact on low student speaking skills. The purpose of the study was to investigate the influence of peer assessment of student speech skills in the second semester of Economics Development of STIE Muhammadiyah JambiThe design of this research is a quasi experimental with a posttest-only control group design. The population of the study was the semester II student of Economics Development of STIE Muhammadiyah Jambi year 2018/2019. The population consisted of 75 students. This research sample was class A as the experimental class and B as the control class. Both classes was taken the value of the speaking test which then be compared. The results of this study showed that students taught using peer assessment had better speaking skills than students taught using the teacher assessment.